High Capability of Pentagalloylglucose (PGG) in Inhibiting Multiple Types of Membrane Ionic Currents - Chang, Wei-Ting (Int J Mol Sci, 2020)
Pentagalloyglucose (PGG, penta-O-galloyl-β-d-glucose; 1,2,3,4,6-pentagalloyl glucose), a pentagallic acid ester of glucose, is recognized to possess anti-bacterial, anti-oxidative and anti-neoplastic activities. However, to what extent PGG or other polyphenolic compounds can perturb the magnitude and/or gating of different types of plasmalemmal ionic currents remains largely uncertain. In pituitary tumor (GH(3)) cells, we found out that PGG was effective at suppressing the density of delayed-rectifier K(+) current (I(K(DR))) concentration-dependently. The addition of PGG could suppress the density of proton-activated Cl(−) current (I(PAC)) observed in GH(3) cells. The IC(50) value required for the inhibitory action of PGG on I(K(DR)) or I(PAC) observed in GH(3) cells was estimated to be 3.6 or 12.2 μM, respectively, while PGG (10 μM) mildly inhibited the density of the erg-mediated K(+) current or voltage-gated Na(+) current. The presence of neither chlorotoxin, hesperetin, kaempferol, morin nor iberiotoxin had any effects on I(PAC) density, whereas hydroxychloroquine or 4-[(2-butyl-6,7-dichloro-2-cyclopentyl-2,3-dihydro-1-oxo-1H-inden-5yl)oxy] butanoic acid suppressed current density effectively. The application of PGG also led to a decrease in the area of voltage-dependent hysteresis of I(PAC) elicited by long-lasting isosceles-triangular ramp voltage command, suggesting that hysteretic strength was lessened in its presence. In human cardiac myocytes, the exposure to PGG also resulted in a reduction of ramp-induced I(K(DR)) density. Taken literally, PGG-perturbed adjustment of ionic currents could be direct and appears to be independent of its anti-oxidative property.